DEVELOPING HOTS-BASED READING ASSESSMENT FOR SENIOR HIGH SCHOOL STUDENTS: VALIDITY, RELIABILITY, AND CLASSROOM PRACTICALITY EVIDENCE - Ilfi Nur Diana (Sensei International Journal of Education and Linguistic, 2025)
In the era of Merdeka Curriculum the students are demanded to have higher order thinking skills, but the reading questions made by the teachers are still dominated by low level questions. This study discusses the development of HOTS-based reading assessment for senior high school students. The study used research and development. The data were collected through expert validation and test trial to the students. The data were analyzed by using validity and reliability analysis. The result shows that the HOTS-based reading assessment that was developed is valid and reliable and can be used in the classroom. Therefore the teachers are suggested to use HOTS-based reading assessment so that the thinking skill of the students can be improved.